Effects of the STAMP-inhibitor asciminib on T cell activation and metabolic fitness compared to tyrosine kinase inhibition by imatinib, dasatinib, and nilotinib - Häselbarth, Lukas; Karow, Axel; Mentz, Kristin; Böttcher, Martin; Roche-Lancaster, Oisin; Krumbholz, Manuela; Jitschin, Regina; Mougiakakos, Dimitrios; Metzler, Markus (Cancer Immunology, Immunotherapy, 2023)
T cell function is central to immune reconstitution and control of residual chronic myeloid leukemia (CML) cells after treatment initiation and is associated with achieving deep molecular response as a prerequisite for treatment-free remission, the ultimate therapeutic goal in CML. ATP-pocket-binding tyrosine kinase inhibitors (TKIs) like imatinib, dasatinib, and nilotinib are widely used for treating CML, but they have shown to inhibit T cell function as an “off-target” effect. Therefore, we tested asciminib, the first-in-class BCR::ABL1 fusion protein inhibitor specifically targeting the ABL myristoyl pocket (STAMP) and compared its effects on T cell function with imatinib, dasatinib, and nilotinib. Whereas all four TKIs inhibited the expression of the co-stimulatory protein CD28, the amino acid transporter CD98, proliferation, and secretion of pro-inflammatory cytokines IFNγ, IL-6, and IL-17A upon T cell stimulation, asciminib had less impact on PD-1, activation markers, and IL-2 secretion. T cells treated with asciminib and the other TKIs maintained their ability to mobilize their respiratory capacity and glycolytic reserve, which is an important surrogate for metabolic fitness and flexibility. Overall, we found milder inhibitory effects of asciminib on T cell activation, which might be beneficial for the immunological control of residual CML cells.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Activity; Asciminib; CML; Metabolism; T cell; TKI

Synergistic lethality in chronic myeloid leukemia – targeting oxidative phosphorylation and unfolded protein response effectively complements tyrosine kinase inhibitor treatment - Häselbarth, Lukas; Gamali, Sara; Saul, Domenica; Krumbholz, Manuela; Böttcher-Loschinski, Romy; Böttcher, Martin; Zou, Deyu; Metzler, Markus; Karow, Axel; Mougiakakos, Dimitrios (BMC Cancer, 2023)
Chronic myeloid leukemia (CML) is effectively treated with tyrosine kinase inhibitors (TKIs), targeting the BCR::ABL1 oncoprotein. Still, resistance to therapy, relapse after treatment discontinuation, and side effects remain significant issues of long-term TKI treatment. Preliminary studies have shown that targeting oxidative phosphorylation (oxPhos) and the unfolded protein response (UPR) are promising therapeutic approaches to complement CML treatment. Here, we tested the efficacy of different TKIs, combined with the ATP synthase inhibitor oligomycin and the ER stress inducer thapsigargin in the CML cell lines K562, BV173, and KU812 and found a significant increase in cell death. Both, oligomycin and thapsigargin, triggered the upregulation of the UPR proteins ATF4 and CHOP, which was inhibited by imatinib. We observed comparable effects on cell death when combining TKIs with the ATP synthase inhibitor 8-chloroadenosine (8-Cl-Ado) as a potentially clinically applicable therapeutic agent. Stress-related apoptosis was triggered via a caspase cascade including the cleavage of caspase 3 and the inactivation of poly ADP ribose polymerase 1 (PARP1). The inhibition of PARP by olaparib also increased CML death in combination with TKIs. Our findings suggest a rationale for combining TKIs with 8-Cl-Ado or olaparib for future clinical studies in CML.
CRIS-Team Scopus Importer:2023-12-15
Keywords: 8-chloroadenosine; ATF4; Caspase 3; CML; Olaparib; Oligomycin; Oxidative phosphorylation; PARP; Thapsigargin; TKI; UPR

Targeting metabolism effectively complements tyrosine kinase inhibitor treatment of chronic myeloid leukemia - Häselbarth, Lukas; Saul, Domenica; Krumbholz, Manuela; Mougiakaos, D.; Metzler, Markus; Karow, A. (KLINISCHE PADIATRIE, 2022)
CRIS-Team WoS Importer:2022-07-08